2011
DOI: 10.3233/jad-2011-110212
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytical Sample Handling and Sample Stability Testing for the Neurochemical Dementia Diagnostics

Abstract: Preanalytical sample handling and storage procedures play an extremely important role in reliably measuring neurochemical dementia diagnostics (NDD) biomarkers: Aβ(1-40), Aβ(1-42), Tau, and pTau181. To test different handling and storage conditions, the following protocols were applied: (a) storage at room temperature for one week, (b) deep-freezing and thawing up to three cycles, (c) deep-freezing, thawing and keeping under +4°C for two days before the analysis, and (d) long-term stability of a deeply frozen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 12 publications
6
50
1
Order By: Relevance
“…Bjerke et al (6 ) stated that storage at room temperature for Ͼ24 h did not significantly affect A␤ concentrations in comparison to both fresh samples and storage at Ϫ80°C until analysis. Another study found relatively stable CSF biomarker concentrations even after 4 days, although unsystematic variation increased over time (18 ). In contrast to this, A␤ has been found to decrease during the first 48 h (11 ) or, more in line with the present study, even to increase within 24 h (14 ).…”
Section: Freezing Delaycontrasting
confidence: 56%
See 1 more Smart Citation
“…Bjerke et al (6 ) stated that storage at room temperature for Ͼ24 h did not significantly affect A␤ concentrations in comparison to both fresh samples and storage at Ϫ80°C until analysis. Another study found relatively stable CSF biomarker concentrations even after 4 days, although unsystematic variation increased over time (18 ). In contrast to this, A␤ has been found to decrease during the first 48 h (11 ) or, more in line with the present study, even to increase within 24 h (14 ).…”
Section: Freezing Delaycontrasting
confidence: 56%
“…From long-term stability studies, it is already known that A␤ 1-42 concentrations in samples frozen at Ϫ80°C are stable for at least 2 years (6,18 ), as are concentrations of T-tau and P-tau 181P when stored at Ϫ20°C for at least for 2 and 4 years, respectively (12,18 ). A storage artifact is seen for cystatin C analysis after freezing at Ϫ20°C, but not at Ϫ80°C (24 ).…”
Section: Freezing Temperaturementioning
confidence: 99%
“…A small part of the overall variability was caused by within-run variability (CV, ,5%-10%, which is in agreement with previous reports and information from kit vendors regarding assay performance [21][22][23]). The within-laboratory longitudinal variability was larger (CV, 5%-19%), which is also in agreement with previous reports [8,24]. In analysis of variance, between-laboratory variability was a major contributor (19%-28%) to the overall variability.…”
Section: Discussionsupporting
confidence: 81%
“…Considerably, CSF Ab peptides have been reported to be more stable over a storage period of 2-5 days [15,17,18] as measured with distinct methods. These results are in line with our own observations measuring CSF Ab peptides under the conditions of the Ab-SDS-PAGE/immunoblot after samples were stored for up to 48 h. Thus, assay specifications of the Ab-SDS-PAGE/immunoblot are unlikely to account for the reported decrease in Ab peptides after sample storage in plasma and serum.…”
Section: Discussionmentioning
confidence: 99%